ISSUES OF IMPROVING LENDING TO SMALL AND MEDIUM-SIZED BUSINESSES (Multidisciplinary Journal of Science and Technology, 2024)
Improvement of lending to small and medium-sized business entities and their role in the country's economy, as well as the most important sector in providing employment to the population, were mentioned. Also, today's statistical indicators of small and medium-sized businesses are presented.